2011
DOI: 10.1021/om2006722
|View full text |Cite
|
Sign up to set email alerts
|

Insertion of Isocyanate and Isothiocyanate into the Ln–P σ-Bond of Organolanthanide Phosphides

Abstract: The synthesis, structure, and reactivity of organoyttrium phosphides toward phenyl isocyanate (PhNCO) and phenyl isothiocyanate (PhNCS) are described. Reaction of (TpMe2)CpYCH2Ph(THF) (TpMe2 = tris(3,5-dimethylpyrazolyl)borate; Cp = C5H5) with 1 equiv of HPPh2 in THF at ambient temperature gives an organoyttrium phosphide (TpMe2)CpYPPh2(THF) (1). Treatment of 1 with 1 equiv of PhNCO in THF at ambient temperature results in monoinsertion of PhNCO into the Y–P σ-bond to yield complex (TpMe2)CpY[OC(PPh2)NPh](THF)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 73 publications
0
32
0
Order By: Relevance
“…9 However, isocyanurates' principal application is in the construction industry; they are the key component in rigid polyurethane foams which are used ubiquitously as insulation boards and are responsible for their mechanical and thermosetting properties. 10 Isocyanates can be trimerized by amines, 11 phosphines, 12-15 N-heterocyclic carbenes, 16 inorganic salts, 17 phosphides, 18,19 and main group and transition metal complexes, [20][21][22][23][24][25][26][27][28] but existing catalysts often require high catalyst loadings, high temperatures (e.g. Z100 1C for amines and halides), 11,17 can give a mixture of oligomers, and/or fail to trimerize both alkyl and aryl isocyanates.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…9 However, isocyanurates' principal application is in the construction industry; they are the key component in rigid polyurethane foams which are used ubiquitously as insulation boards and are responsible for their mechanical and thermosetting properties. 10 Isocyanates can be trimerized by amines, 11 phosphines, 12-15 N-heterocyclic carbenes, 16 inorganic salts, 17 phosphides, 18,19 and main group and transition metal complexes, [20][21][22][23][24][25][26][27][28] but existing catalysts often require high catalyst loadings, high temperatures (e.g. Z100 1C for amines and halides), 11,17 can give a mixture of oligomers, and/or fail to trimerize both alkyl and aryl isocyanates.…”
mentioning
confidence: 99%
“…It is common for isocyanate trimerization to proceed via nucleophilic attack on the isocyanate carbon, 10 and there are several examples of isolated species arising from the insertion of isocyanates into metal-ligand bonds. 18,23,[37][38][39] This leads us to propose a catalytic cycle (Scheme 3) based on a repeated coordination-insertion mechanism. ¶ A crucial component of this mechanism is that pyridyl dissociation must occur before the isocyanate can associate to allow the 1,2-migratory insertion of the methoxide onto the isocyanate carbon; importantly, de-coordination of the pyridyl is facile (S to INT1: DG = +16 kJ mol À1 ).…”
mentioning
confidence: 99%
“…Molecular structure was confirmed by X‐ray crystallographic analysis, which revealed that 3 adopted a distorted‐octahedral structure (Figure ). The Y–S bond length (2.796(7) Å) of 3 is comparable to those of Y–S bond in Cp 2 Y[SC(PPh 2 )NPh](THF) (2.773(6) Å) and (TpMe 2 )CpY [SC(PPh 2 )NPh] (2.823(6) Å) . However, the Y–S distance of 3 is considerable longer than the corresponding values in 1,4‐C 6 H 4 [C(NC 6 H 3 i Pr 2 ‐2,6) 2 Y{SC(CH 2 C 6 H 4 NMe 2 ‐ o )NPh} 2 ] 2 (2.708(12) Å)[8a] and L Y{SC(CH 2 C 6 H 4 NMe 2 ‐ o )NPh} 2 (2.715(9) Å).…”
Section: Resultsmentioning
confidence: 74%
“…The insertion of E-H bonds (E = N, P, S) across heterocumulene systems, such as carbodiimides, isocyanates and isothiocyanates represents and atom-economic route for the generation of a variety of organic synthons, such as guanidines and phosphaguanidines. Therefore this process has been widely studied over the past decade using lanthanide catalysts [100][101][102][103][104][105][106]. However, only recently Eisen et al, have reported the application of a thorium catalyst for this type of atom-economic catalytic transformation [107].…”
Section: Insertion Of Nucleophilic E-h (E = N P S) Bonds Into Hetermentioning
confidence: 99%